2012
DOI: 10.1016/j.febslet.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The ribonuclease l‐dependent antiviral roles of human 2′,5′‐oligoadenylate synthetase family members against hepatitis C virus

Abstract: a b s t r a c tThe latent ribonuclease RNase L and the interferon-inducible 2 0 ,5 0 -oligoadenylate synthetase (OAS) have been implicated in the antiviral response against hepatitis C virus (HCV). However, the specific roles of these enzymes against HCV have not been fully elucidated. In this study, a scarce endogenous expression and RNA degrading activity of RNase L in human hepatoma Huh7 cells enabled us to demonstrate the antiviral activity of RNase L against HCV replication through the transient expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…It has been reported that OAS3 is constitutively expressed in Huh7 cells, and is significantly induced following IFN treatment. OAS3 may exert its anti-HCV replication through the activation of RNase L in the early stage of antiviral response [12]. The MX1(A) protein has also been shown to be involved in HCV induced stress granules formation that regulate HCV replication through virus assembly and egress [13].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that OAS3 is constitutively expressed in Huh7 cells, and is significantly induced following IFN treatment. OAS3 may exert its anti-HCV replication through the activation of RNase L in the early stage of antiviral response [12]. The MX1(A) protein has also been shown to be involved in HCV induced stress granules formation that regulate HCV replication through virus assembly and egress [13].…”
Section: Resultsmentioning
confidence: 99%
“…The Neandertal-introgressed allele encodes a protein variant (p46) that is associated with higher enzymatic activity [36]. The adaptive potential of this variant is supported by the observation that this variant (or other variants in strong LD with it) was shown to be associated with: (1) reduced infection and replication rates of West Nile virus ([38], but see [39]); (2) improved resistance to hepatitis C virus (HCV) infection [40, 41]; and (3) variable symptomology of tick-borne encephalitis (TBE) virus-induced disease (homozygous individuals for the Neandertal haplotype show the most severe symptoms of TBE). Strikingly, West Nile, hepatitis C, and TBE are all members of the Flaviviridae family, suggesting that Flaviviruses might have been the main drivers of selection in OAS1 .…”
Section: Discussionmentioning
confidence: 99%
“…In Hepatitis C virus (HCV) patients it was found that patients with AA in rs10774671 were non-responders to interferon treatment and they had a progressive HCV disease [25]. When overexpressing the individual OAS proteins in human hepatoma Huh7 cells, OAS1 p46 as well as OAS3 p100 could inhibit HCV replication, whereas the OAS1 isoforms p42, p48 and p52 and the OAS2 isoforms p69 and p71 could not [26]. This suggests that expression of p46 caused by the G allele of the rs10774671 SNP is protective of HCV infection, or the A allele could be a risk factor.…”
Section: Introductionmentioning
confidence: 99%